Establishment of Axenic Explants and Callus Induction of Vernonia amygdalina Del. - Kong, Yee Yan Eveline; Sani, Hamsawi (Borneo Journal of Resource Science and Technology, 2017)
Vernonia amygdalina is a plant with great medicinal potentials due to the phytochemicals it possesses. The establishment of axenic culture and callus induction are important as the primary steps to acquire callus and cell suspension cultures which are prospective to be used as alternatives in the production of phytochemicals. The effect of different regimes of sterilization unveiled that explants treated with mercuric chloride showed significant difference in the mean number of axenic explants, but observations of serious necrosis in all explants that later lead to death were recorded. Whilst, the explants treated with Clorox® were not significantly difference in the mean number of axenic explants but the explants obtained were healthy and the growth was sustained. For callus induction, there was no significant difference in the callus induction frequency (CIF) among different concentrations of 2,4-D or picloram. In conclusions, the explants were recommended to be surface sterilized with 15% of Clorox® for 15 minutes as it was more economical and less time consuming. Whereas, MS media supplemented with 0.5 mg/L 2,4-D or 0.5 mg/L picloram would be a better choice for callus induction due to observation of root formation at lower concentrations of 2,4-D.